Rice Breeding Strategies in the Philippines - Palanog, Alvin D.; Mondejar, Cielo Luz C.; Bello, Gerald E.; Calayugan, Mark Ian C; Palanog, May Osano; Caguiat, Xavier Greg I.; Ferrer, Marilyn C.; Sta. Ines, Leo T. (Journal of Scientific Agriculture, 2020)
Rice is a major staple in the Philippines. The major goal of the rice sector in the country is to increase its productivity to meet the ever growing demand for rice. Breeding is one of the potential solutions to achieve rice self-sufficiency in the country. Rice variety development is led by research institutions such as PhilRice, IRRI, UPLB, and private companies and each adapts various breeding strategies. Rice variety normally takes 10-12 years of a journey from breeding to release and more than 300 varieties have been developed and released that were suited for various rice ecosystems. Sufficient varieties were available for production and this led to continuous in rice production for the past decade. However, yield increment has plateaued. To meet the increasing demand for rice, achieve self-sufficiency, and particularly, break the yield barrier (plateau) and achieve a leap in yield potential, breeding institutions particularly PhilRice should embrace new advances and technologies in rice breeding. The introduction of the concept of transforming breeding into a “factory line” type encouraging rapid generation advance, earlier multi-location trials, and increasing selection pressure, and employing genomic selection (GS) in handling a large quantity of materials/populations can improve breeding efficiency and outputs significantly.